ANALISIS KOMPARASI KEPUASAN KONSUMEN YANG MEMBELI SMARTPHONE CHINA DI GERAI RESMI DAN BLACK MARKET - Febrianur Ibnu Fitroh Sukono Putra; Diana Aqmala; Aufa Marzuq Alwi; Inggrit Faza Saputra; Sisca Dian Rahmawati (Jurnal Manajemen Indonesia, 2021)
The research aims to analyze the main factor determining Chinese Smartphone Customer Satisfaction. The population of this research were all customers who purchased Chinese smartphones in Surakarta, Semarang, Pemalang, Purworejo, Grobogan. The sampling technique used purposive sampling by taking 200 official store customers and 200 black-market customers. The data collection method was a survey by personal questionnaire with an data analysis used multiple linear regression and different tests (independent sample T-test). The results obtained several findings that the price perception, product quality, and marketplace significantly affect customer satisfaction. Finally, there are differences in customer satisfaction felt purchased Chinese smartphones in the official store with the black market. Keywords— Chinese smartphone; Customer Satisfaction; Product Quality; Price Perception; and Marketplace.